Fluorine-Modulated MXene-Derived Catalysts for Multiphase Sulfur Conversion in Lithium–Sulfur Battery - Gu, Qinhua; Cao, Yiqi; Chen, Junnan; Qi, Yujie; Zhai, Zhaofeng; Lu, Ming; Huang, Nan; Zhang, Bingsen (Nano-Micro Letters, 2024)
Fluorine owing to its inherently high electronegativity exhibits charge delocalization and ion dissociation capabilities; as a result, there has been an influx of research studies focused on the utilization of fluorides to optimize solid electrolyte interfaces and provide dynamic protection of electrodes to regulate the reaction and function performance of batteries. Nonetheless, the shuttle effect and the sluggish redox reaction kinetics emphasize the potential bottlenecks of lithium–sulfur batteries. Whether fluorine modulation regulate the reaction process of Li–S chemistry? Here, the TiOF/Ti3C2 MXene nanoribbons with a tailored F distribution were constructed via an NH4F fluorinated method. Relying on in situ characterizations and electrochemical analysis, the F activates the catalysis function of Ti metal atoms in the consecutive redox reaction. The positive charge of Ti metal sites is increased due to the formation of O–Ti–F bonds based on the Lewis acid–base mechanism, which contributes to the adsorption of polysulfides, provides more nucleation sites and promotes the cleavage of S–S bonds. This facilitates the deposition of Li2S at lower overpotentials. Additionally, fluorine has the capacity to capture electrons originating from Li2S dissolution due to charge compensation mechanisms. The fluorine modulation strategy holds the promise of guiding the construction of fluorine-based catalysts and facilitating the seamless integration of multiple consecutive heterogeneous catalytic processes. Highlights: 1 By introducing fluorine modulation into MXene, a new MXene-derived material TiOF/Ti3C2 was successfully synthesized with a distinctive three-dimensional structure and a tailored F distribution. 2 In situ characterizations and electrochemical analyses demonstrate that TiOF/Ti3C2 catalysts effectively coupled the multiphase sulfur species conversion processes. 3 The investigations reveal that the theoretical basis of the fluorine catalysis in Li–S batteries originated from Lewis acid–base mechanisms and charge compensation mechanisms.